PERENCANAAN TARIF ANGKUTAN UMUM JURUSAN PALANGKA RAYA – SEPANG KOTA DALAM MASA PANDEMI ( COVID-19 ) (Planning Of Public Transport Rates For Palangka Raya – Sepang City In A Pandemic Period ( Covid-19 ) - Yosevina .; Antoni Widodo (Fakultas Teknik Universitas Kristen Palangka Raya, 2022)
k General force is a means of transportation needed by the majority of urban/regional people, it is impossible for a city/region to live without public transportation. Taxi public transportation is one of the alternative public transportation in the district area, which provides other services and is not the same as other transportation. The purpose of this study is to determine the amount of Vehicle Operating Costs (BOK) for public transportation from Palangka Raya City to Sepang City Village, as well as to find out the amount of passenger fares that are in accordance with the Vehicle Operational Costs (BOK) incurred. Based on the results of the analysis of Vehicle Operating Costs (BOK), the total basic costs per day for general passengers from Palangka Raya City to Sepang City Village are: Avanza Veloz car of Rp. 297,848.75/vehicle/day, the basic fare for a general passenger from Palangka Raya City to Sepang City Village is Rp. 59,569,75/org/rit. The basic fare for public transportation heading from Palangka Raya City to Sepang City Village is IDR 65,526.72/org/rit. While the tariff at the time of this research was Rp. 150,000 total revenue per day at a rate of Rp. 150,000 x the number of trips per day was Rp. 750.000,-. /org/rit. From the first transportation vehicle above, it provides a proper opinion for the manager/owner, for passengers the price is reasonable, feasible and affordable because it is in accordance with the time and distance traveled. Keywords: Public Transportation / Taxi, Vehicle Operating Cost (BOK) per km, Total basic cost per